Ethnoscience Integrated Flipbook Learning Media on Living Things Classification Materials - Mega Elvianasti; Novia Heza Lestari; Meitiyani Meitiyani; Maesaroh Maesaroh (Journal of Innovation in Educational and Cultural Research, 2023)
Many researchers have developed learning media. However, learning media with ethnoscience content in Betawi is still little developed. This study aims to develop learning media flipbooks with ethnoscience content on the classification of living things. The research method used was the ADDIE development method. The results showed that the feasibility test on media development was declared very valid by media and material experts with a percentage of 91.30%. While the feasibility test conducted by respondents was declared very valid as well, with a percentage of 87.63%, In accordance with the eligibility criteria table, it can be concluded that the ethnoscience-integrated flipbook learning media is declared very feasible to use in learning the Classification of Living Things material. The implication of this research is that the ethnoscience-charged media developed can be used in biology learning. In addition, the ethnoscience-integrated flipbook media can introduce Betawi local wisdom to students. However, ethnoscience-integrated flipbook learning media have not been tested for effectiveness. Research is needed to test the effectiveness of ethnoscience-integrated flipbook learning media.